Alimentos fermentados - PIVETTA, Márcia Uliana; GONÇALVES, Rafael Canovas (042, 2023)
Este projeto tem como objetivo valorizar o processo dos alimentos fermentados com base em conceitos históricos e culturais que influenciaram a maneira de consumo. Basicamente se resume na transformação dos açúcares presentes nos alimentos em ácidos, o que resulta além da sua preservação, características sensoriais, como sabores, texturas e aromas distintos. Além disso, oferecem diversos benefícios para a saúde e o meio ambiente. O processo de fermentação pode ocorrer em diversos alimentos como: frutas, legumes, grãos, leite entre outros. Os alimentos fermentados têm grande importância na gastronomia, e está presente na sociedade há séculos.

This project aims to recognize and appreciate the significance of fermented foods by exploring their historical and cultural influences on consumption practices. Essentially, fermentation involves the conversion of sugars found in various food items into acids, resulting in not only preservation but also the development of sensory characteristics such as flavors, textures, and distinct aromas. Moreover, fermented foods offer numerous health and environmental benefits. The fermentation process can occur in a wide range of foods, including fruits, vegetables, grains, milk, and more. Fermented foods hold immense importance in gastronomy and have been an integral part of society for centuries.
Keywords: Alimentos fermentados; Alimentos; Turismo, Hospitalidade e Lazer